Utilization of egg-laying hens (Gallus Gallus domesticus) for production of ingredients for human consumption and animal feed - Hjellnes, Veronica (BMC Biotechnol, 2020)
BACKGROUND: In Norway, 3 million discarded egg-laying hens are destructed annually, which equals 1500 tons pure hen meat. Due to the slaughter methods used, this raw material is handled as a high-risk waste, while in reality it constitutes a source of valuable components like proteins and lipids. METHODS: This study assess different processing methods (thermal treatment, enzymatic hydrolysis and silaging) for utilization of discarded egg-laying hens for the production of ingredients for human consumption and animal feed. The processing methods were evaluated on the basis of quantity and quality of the obtained products. RESULTS: Thermal treatment and enzymatic hydrolysis resulted in extraction of good quality lipids from the raw material. The separated oil (50.1–82.3% of the total lipid content in the raw material) was of high quality based on the content of free fatty acids (≤ 1.0%) and total oxidation value (≤ 3.9). Enzymatic hydrolysis also enabled separation of protein in the form of protein hydrolysate. Addition of Protamex and Papain+Bromelain significantly (p ≤ 0.05) increased the protein content (85.1–94.6%) and decreased the lipid content (0.3–1.1%) in the hydrolysate compared to autolysis (protein content: 64.8–72.3%, lipid content: 1.0–2.6%). Silaging increased the protein digestibility (63.2–79.7% compared to 57.3–66.2% for untreated raw material), and thus constitutes a good method for utilizing the protein content of the raw material for animal feed. CONCLUSION: The biotechnological processing methods thermal treatment, enzymatic hydrolysis and silaging can be used to increase the utilization of discarded egg-laying hens for production of ingredients for human consumption and animal feed.